STRATEGY OF TOURISM VILLAGE DEVELOPMENT BASED ON LOCAL WISDOM - Hisnuddin Lubis; Nelly Rohmatillah; Dania Rahmatina (Jurnal Ilmu Sosial dan Humaniora, 2020)
One of the current development alternatives is Tourism Development, mainly rural tourism. The fundamental problem is how the right strategy to achieve these development goals. The development of a tourism village can consider the potential of local, government, private, formal, and informal economic sectors and internal and external interest groups. This study seeks to reveal the right strategy in developing tourism in the village of Telaga Biru Bangkalan based on local resources. This study uses a literature review with a tourism development approach within a qualitative method frame. The data is in the form of interpretations of research results published in national and international journals that are analyzed descriptively to produce conclusions. The result of this study is the formulation of a form of tourism in a tour package that includes batik schools, traditional Madurese games, and traditional art performances, regional culinary specialties, and lodging with the Tanean Lanjhang concept. The Strategy for the Implementation of Batik Tourism Village program through stages, including First, increasing community capacity with knowledge as the main target of Knowledge, Attitudes, and Practices (KAP) of the local community through community-based education and training activities (CBT). Second, human resource inventories for local guides, Batik school instructors, traditional Madurese game teams, Madurese culinary providers. Third, the institutionalization of tourism village management at the village level will be responsible for the sustainability of the tourism village. Fourth, the efforts of bridging and linking with the Bangkalan tourism office and investors. Fifth, cooperation with the travel agencies in Madura. Sixth, branding, and promotion through social media and tourism village websites. Implementing this strategy will create a new tourist destination, “Batik tourism village” in a different form and will increase the community economy and regional income.